Batch adsorption of herbicides from aqueous solution onto diverse reusable materials and granulated activated carbon. (1st December 2022) - McGinley, J.; Healy, M.G.; Ryan, P.C.; Mellander, P.-E.; Morrison, L.; O'Driscoll, J. Harmon; Siggins, A.
Abstract: This study reports the kinetics and isotherms of the adsorption of five herbicides, MCPA, mecoprop-P, 2, 4-D, fluroxypyr and triclopyr, from aqueous solutions onto a range of raw and pyrolysed waste materials originating from an industrial setting. The raw waste materials investigated demonstrated little capability for any herbicide adsorption. Granulated activated carbon (GAC) was capable of the best removal of the herbicides, with >95% removal observed. A first order kinetic model fitted the data best for GAC adsorption of 2, 4-D, while a pseudo-first order model fitted the data best for GAC adsorption of fluroxypyr and triclopyr, indicating that adsorption was via physisorption. A pseudo-second order kinetic model fitted the GAC adsorption of MCPA and mecoprop-P, which is indicative of chemisorption. The adsorption of the herbicides in all cases was best described by the Freundlich model, indicating that adsorption occurred onto heterogeneous surfaces. Graphical abstract: Image 1 Highlights: Adsorption of herbicides by waste materials and activated carbon investigated. Activated carbon displayed best adsorption of herbicides. Adsorption occurred via physisorption or chemisorption. Adsorption of all herbicides best described by Freundlich model.